Very low birth weight infants in a Portuguese Neonatal Intensive Care Unit: a comparative study with the Vermont Oxford Network - Ana R. Fernandes; Paulo Soares; Gorett Silva; Filipa Flor-de-Lima; Maria Beatriz Guedes; Hercília Guimarães (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Introduction: It is our goal to analyze the neonatal data from a Level III Unit and compare them with the overall data from the Vermont Oxford Network (VON).